CNS germ cell tumors: Pattern of failure and effects of radiation volume - Imjai Chitapanarux (2018)
This retrospective study was conducted to evaluate local control and overall survival after radiotherapy for patients with intracranial germ cell tumors and to investigate the influence of irradiated field on treatment outcome. Thirty-two patients with surgically confirmed or suspected primary intracranial germ cell tumors (GCT) treated at the Division of Therapeutic Radiology and Oncology, Chiang Mai University, Chiang Mai, Thailand between January 1988 and December 1999 were reviewed. Seven patients were not included in the analysis of treatment outcome and survival due to incompleteness of radiation treatment or death before the end of treatment. The median follow up time of 39.5 months (range from 2.3 months to 136.1 months). Median age at diagnosis was 16.5 years with 23 males and 9 females. Patients were irradiated to the primary tumor with an adequate margin in 7 patients, to the whole brain with a cone down boost in 8 patients. Craniospinal irradiation (CSI) was performed in 10 patients. For the 25 evaluable patients, 5 year overall survival was 86.4%. Five-year disease free survival was 72.9%. Five year overall survival rates were 83.1% and 90.0% for the germinoma and nonbiopsied group. (p-value = 0.6052). Routine prophylactic CSI was not given with a spinal only failure rate of 33.3%. Five-year overall survival were 85.7%, 87.5%, 85.7% for CSI, whole brain irradiation with boost and local field irradiation (p-value = 0.9037). Five-year disease free survival were 85.7%, 72.9%, 85.7% for CSI, WBRT, and local field (p-value = 0.6403). This retrospective study suggests that definitive radiation therapy is effective in controlling germinoma, and cure rates are excellent with irradiation alone. Craniospinal irradiation can eliminate the risk of relapse especially in patients who had incomplete diagnostic craniospinal evaluation.